LncRNA MANCR is downregulated in non-small cell lung cancer and predicts poor survival - Yunming Tao; Jie Liu; Wenxiao Qiu; Yuanyuan Li (Discover Oncology)
Abstract Background It is known that genomic instability contributes to cancer development. Mitotically associated long non-coding RNA (MANCR) has been reported to promote genomic stability, suggesting its involvement in cancers. Therefore, this study was conducted to investigate the role of MANCR in non-small cell lung cancer (NSCLC). Methods After NSCLC (n = 60) and control (healthy subjects, n = 60) plasma samples, as well as NSCLC and paired non-tumor tissues from patients were collected, the levels of MANCR expression in plasma and tissues was detected using quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). Then the correlations of MANCR expression with clinical stages were confirmed. The diagnostic values of MANCR in both plasma and tissue samples for stage I/II NSCLC were analyzed using Receiver Operating Characteristic (ROC) curves. All NSCLC patients were monitored for 5 years to investigate the role of MANCR in the prediction of patients’ survival. Results MANCR expression was downregulated in both NSCLC plasma and tissue of NSCLC patients compared to controls (P < 0.05). Decreased MANCR expression levels from stage I to IV were observed. However, MANCR expression in non-tumor tissue was not significantly different between different stages (P > 0.05). Additionally, stage I/II NSCLC patients were separated from controls using MANCR in plasma and tumor tissues as biomarkers. Lower MANCR levels in plasma and tumor were closely correlated with patients’ higher mortality rate. Conclusion MANCR is down-expressed in NSCLC patients and may serve as a diagnostic and prognostic biomarker for NSCLC.